God's Prime Directive: Non-Interference and Why There Is No (Viable) Free Will Defense - Johnson, David Kyle (Religions, 2022)
In a recent book and article, James Sterba has argued that there is no free will defense. It is the purpose of this article to show that, in the most technical sense, he is wrong. There is a version of the free will defense that can solve what Sterba (rightly) takes to be the most interesting and severe version of the logical problem of moral evil. However, I will also argue that, in effect (or, we might say, in practice), Sterba is correct. The only working version of the free will defense requires embracing a view that entails consequences theists traditionally have not and cannot accept. Consequently, the one and only free will solution is not viable. Unless some other solution can be found (Sterba argues there is none), the logical problem of evil, as Sterba understands it, either commits one to atheism, or a version of theism that practically all theists would regard as a heresy.